Reforming land rights in Africa - Ngaido, Tidiane (International Food Policy Research Institute, 2004)
Advocates of reforms in land rights and land markets frequently posit two important hypotheses: (1) African countries must grant land titles to farmers because titles increase land tenure security and facilitate access to input, land, and financial markets; and (2) land markets constitute the most efficient mechanism for allocating resources and improving access to productive resources by the poor, especially women and other marginalized groups... Research must focus on understanding the dynamics of land values in the different markets for land rights and devise ways to improve the marketability of customary rights through simple processes that also increase the demand for agricultural land and effectively contribute to the reform of land rights. -- from Text